1962
DOI: 10.1063/1.1733154
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Filling of a Line by Intervals Placed at Random and Its Application to Linear Adsorption

Abstract: A line with integral length n is filled sequentially at random with nonoverlapping intervals of integral length a, their end points having integer coordinates. It is shown that, as n tends to infinity, the average value of the length left vacant tends asymptotically to (n+a) A1(a) while its variance tends to (n+a) × aA2(a), where A1(a) and A2(a) are constants whose values are given numerically for all a; these asymptotic results are accurate to four significant figures for n/a>8. Some results are also g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
56
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(64 citation statements)
references
References 11 publications
8
56
0
Order By: Relevance
“…Similarly, the combined results of [5] and [6] showed that the variance ofĨ x has the estimate in (2), once the limit t → ∞ is taken; in this limit,…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Similarly, the combined results of [5] and [6] showed that the variance ofĨ x has the estimate in (2), once the limit t → ∞ is taken; in this limit,…”
mentioning
confidence: 82%
“…In [3], it is observed that one can adapt the technique to the interval packing problem so as to obtain a central limit theorem for any fixed t. The details of a rigorous proof can be found in [2]. Bankovi [1] investigated the distribution of vacant intervals for the parking problem, as did Mackenzie [6] for a discretized version of the problem. This paper generalizes their results to the interval packing problem.…”
mentioning
confidence: 99%
“…What is the expected number of persons to sit down? Solutions to this problem were provided by Friedman, Rothman and MacKenzie [3,7] who show that as n tends to infinity the expected fraction of the seats that are occupied goes to 1 2 − 1 2e 2 . (For a nice exposition of this and related problems see [1].)…”
Section: Related Workmentioning
confidence: 99%
“…The gap distribution for various versions of the random sequential adsorption model has been studied in detail in [8,9] since it has direct consequences among others for the distribution of cracks in brittle materials [10]. In the most simple continuous case (random car parking model) the spacing distribution P (D) behaves like [11]. But the results from London demonstrated clearly that in reality P (D) → 0 as D → 0.…”
Section: Theorymentioning
confidence: 99%